OBSERVASI PERTUMBUHAN SERTA PEMBENTUKAN TUBUH BUAH JAMUR TIRAM PUTIH (Pleurotus ostreatus) PADA MEDIA SERBUK GERGAJI DAN LIMBAH DAUN KAKAO - Umrah, Umrah; Asfiani, Asfiani; Yuniati, Eny; Zainal, Amalia Purnamasari (Biocelebes, 2025)
he title of this research is The observation of the growth and formation of white oyster mushroom fruit body (Pleurotus ostreatus) on sawsdust and cocoa leaf waste media litter which has been carried out in the Microbiology Laboratory, Department of Biology, Faculty of Mathematics and Natural Sciences. The aim of this research is to determine mycelium growth and formation. Fruting bodies of white oyster mushrooms (Pleurotus ostreatus) on a basic medium of sawdust substituted with leaf litter cocoa. This research was designed in a Completely Randomized Design (CRD) consisting of seven treatments and three replications. The treatment media consisted of sawsdust and and cocoa leaf waste (CLW), namely P1 (sawsdust 500g without CLW), P2 (sawsdust 475g + CLW 25g), P3 (sawsdust 450g + CLW 50g), P4 (sawsdust 425g + CLW 75g), P5 (sawsdust 400g + CLW 100g), P6 (sawsdust 375g + CLW 125g), P7 (sawsdust 350g + CLW 150g) 45g rice bran + 5g lime + 500 ml water were added to each treatment. The best growth in observing the mycelium incubation period until it filled the baglog was in treatment (P2) with a time of 43 days, the best growth in the incubation period until pinheads appeared was in treatment (P1) with a time of 53 days, the best treatment for the number or fruit bodies is in treatment (P5) with a value of 8,67, the best treatment for fresh body weight fruit, namely treatment (P5) with a value of 60,67g. The best treatment for fruit body dry weight was treatment (P5) with a value of 11,33g. The media composition corresponds to the best treatment of the seven treatments, namely P5 (400g sawdust + 100g cocoa leaf litter). Because it has the fastest fruit body incubation. The highest number of fruit bodies and the heaviest fresh weight and dry weight.